The KPSS test with outliers (2005)
We investigate the effects of outliers on the KPSS tests. We find that for nonstationary series outliers induce spurious stationarity by lowering the power of these tests. The empirical size of these tests is also found to be sensitive to the location of the outlier. © Springer Science+Business Media, Inc. 2005.